2018
DOI: 10.1021/acssuschemeng.8b03013
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Low Environmental Impact Approach to Prepare Thermally Conductive Nanocomposites Based on Polylactide and Graphite Nanoplatelets

Abstract: In this work, the preparation of nanocomposites based on poly(l-lactide) PLLA and graphite nanoplatelets (GNP) was assessed by applying, for the first time, the reactive extrusion (REX) polymerization approach, which is considered a low environmental impact method to prepare polymer systems and which allows an easy scalability. In particular, ad hoc synthesized molecules, constituted by a pyrene end group and a poly(d-lactide) (PDLA) chain (Pyr-d), capable of interacting with the surface of GNP layers as well … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…This phenomenon demonstrated that Pyr-PCL promotes the dispersion of graphite when the ratio of Pyr-PCL/graphite reaches a critical value, which allows the adsorption of the molecule on the surface of the flakes as well as maintaining the GNP dispersed in DMF, thus avoiding its coalescence. The proven adsorbance of Pyr-PCL onto GNP suggests the possibility to exploit this as a compatibilizer in PCL nanocomposites [22]. Figure 6.…”
Section: Study Of the Graphite Dispersionmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon demonstrated that Pyr-PCL promotes the dispersion of graphite when the ratio of Pyr-PCL/graphite reaches a critical value, which allows the adsorption of the molecule on the surface of the flakes as well as maintaining the GNP dispersed in DMF, thus avoiding its coalescence. The proven adsorbance of Pyr-PCL onto GNP suggests the possibility to exploit this as a compatibilizer in PCL nanocomposites [22]. Figure 6.…”
Section: Study Of the Graphite Dispersionmentioning
confidence: 99%
“…An alternative approach to guarantee strong interactions between non functionalized GRM is the modification of the chemical structure of the macromolecules to promote non-covalent bonding with graphitic surfaces. As such, taking into account the specific interactions that occur between pyrene molecules and the surface of the graphite lamellae [ 18 , 19 ], polymers bearing these functionalities were developed and used for the preparation of composite systems [ 20 , 21 , 22 ]. In particular, considering biopolymers, in a recent work of ours we reported on the development of nanocomposites based on poly( l -lactide) (PLLA) by synthesizing initiators, constituted by a pyrene end group and a poly( d -lactide) (PDLA) chain, capable of interacting with the surface of GNP layers as well as forming stereoblocks during the ring opening polymerization of l -lactide [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the presence of edge-grafted molecular junctions or cross-linkers between graphene nanofillers was experimentally and numerically found to reduce the thermal resistance at the filler-filler interface [35,36]. Furthermore, the controlled chemical functionalization of carbon nanofillers improved the thermal transport across filler-matrix interfaces [37][38][39][40], while reducing the thermal conductivity of the nanofillers at the same time [41].…”
Section: Introductionmentioning
confidence: 99%
“…Compatibilization between GRM nanoplatelets and organic polymers have been widely studied to promote dispersion in the preparation of nanocomposites as well as to tailor their physical properties (Kuilla et al, 2010; Potts et al, 2011; Mittal, 2014; Papageorgiou et al, 2017). Polyaromatic derivatives, mostly based on pyrene or perylene substituted with a dangling chain able to compatibilize toward the organic polymer have been largely studied, including the functionalization of GRM with polymers bearing pyrene groups (Liu et al, 2010; Liang et al, 2012; Tong et al, 2013; Wang et al, 2015; Fina et al, 2018).…”
Section: Introductionmentioning
confidence: 99%